Mechanical properties of hemp-clay and hemp stabilized clay composites. (30th November 2017) - Mazhoud, Brahim; Collet, Florence; Pretot, Sylvie; Lanos, Christophe
Highlights: The efficiency of clay stabilization on mechanical properties is highlighted. The effect of hemp to binder ratio is investigated. The ductile behavior of developed composites is underlined. Abstract: This study aims to develop a new low carbon footprint material using hemp and clay. It investigates the effect of clay stabilization and hemp to binder ratio on mechanical performances. All composites have ductile behavior. Composites with highest hemp to binder ratio show steadily increasing strength with deformation. Hemp stabilized clay composites have better mechanical properties than hemp clay composites. Mechanical properties strongly depend on the hemp to binder ratio. The tensile strength ranges from 0.021 to 0.059 MPa. The compressive strength ranges from 0.39 to 0.68 MPa. The mechanical performance of developed composites meets the requirements of the intended use.